The Application of Nucleic Acid Probe–Based Fluorescent Sensing and Imaging in Cancer Diagnosis and Therapy - Huang, Ge; Su, Chen; Wang, Lijuan; Fei, Yanxia; Yang, Jinfeng (Frontiers in Chemistry, 2021)
It is well known that cancer incidence and death rates have been growing, but the development of cancer theranostics and therapeutics has been a challenging work. Recently, nucleic acid probe–based fluorescent sensing and imaging have achieved remarkable improvements in a variety of cancer management techniques, credited to their high sensitivity, good tolerance to interference, fast detection, and high versatility. Herein, nucleic acid probe–based fluorescent sensing and imaging are labeled with advanced fluorophores, which are essential for fast and sensitive detection of aberrant nucleic acids and other cancer-relevant molecules, consequently performing cancer early diagnosis and targeted treatment. In this review, we introduce the characteristics of nucleic acid probes, summarize the development of nucleic acid probe–based fluorescent sensing and imaging, and prominently elaborate their applications in cancer diagnosis and treatment. In discussion, some challenges and perspectives are elaborated in the field of nucleic acid probe–based fluorescent sensing and imaging.